Behavioural and neural correlates of tinnitus - Berger, Joel I. (2014)
Tinnitus, often defined as the perception of sound in the absence of an external stimulus, affects millions of people worldwide and, in extreme cases, can be severely debilitating. While certain changes within the auditory system have been linked to tinnitus, the exact underlying causes of the phenomenon have not, as yet, been elucidated. Animal models of tinnitus have considerably furthered understanding of the some of the changes associated with the condition, allowing researchers to examine changes following noise exposure, the most common trigger for tinnitus.This thesis documents the development of an animal model of tinnitus, using the guinea pig to examine neural changes following induction of tinnitus.